Finance and Development, December 1967. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1967)
This paper discusses the project financed by the World Bank for controlling the flow of the Chao Phya River in Thailand. Chao Phya is the lifestream of the Thai people. However, this river, and its principal tributaries are, in their natural state, capricious rivers. In the early 1950s, the World Bank began assisting the Thai government in a series of projects designed to break this ancient tyranny of the rivers' violent changes. The paper describes how the river is being tamed for irrigation and navigation, and how they are providing electric power and other benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet